The effectiveness of using spotify to improve students’ listening skills at SMP Panca Budi Medan - Suryanawi, Suryanawi; Sinurat , Crist Nova; Azis, Ananda Rizkia; Tarigan, Sri Ninta; Rahmawati, Rahmawati (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
This study aimed to examine the effectiveness of using Spotify to improve students’ listening skills, specifically through listening to English songs to identify missing words and analyze grammatical structures in the lyrics. A quantitative method with a pre-experimental design was applied, utilizing a one-group pre-test and post-test approach. The participants consisted of 25 ninth-grade students from class IX-2 at SMP Panca Budi Medan. Data were collected through listening tests conducted before and after the treatment. The pre-test results showed a total score of 1090 with an average of 43.6, indicating low listening proficiency. After the treatment using Spotify, the post-test results increased significantly to a total score of 2140, with an average of 85.6. Statistical analysis revealed that the significance value (Sig.) was less than 0.05, confirming that the alternative hypothesis (H?) was accepted and the null hypothesis (H?) was rejected. These results indicate that the use of Spotify was effective in enhancing students’ listening skills. The findings suggest that integrating digital music platforms like Spotify into English language instruction can provide students with engaging and authentic listening experiences. This approach not only increases students’ motivation and enjoyment but also supports their comprehension of real-life language use. Therefore, educators are encouraged to utilize music-based applications as supplementary tools in teaching listening, particularly for learners in EFL (English as a Foreign Language) contexts.